Impact of sous vide cooking on nutritional quality of meat - Aviles, Maria Victoria (2020)
Cooking becomes the meat more digestible, eating, and palatable. However, heat treatment can cause undesirable nutritional changes inmeat, such as loss of minerals and vitamins, oxidation of lipids and changes in some segments of the protein fraction. The use of sous vide processing technology, which refers to cooking vacuum-sealed food in heat-stable plastic pouches under precisely monitored conditions, representsan interesting cooking alternative in terms of retains its natural sensory qualities of meat along with the nutritional value. In this paper, theresearch on the effect of sous vide cooking of meat on its nutritional quality is reviewed.